Comparison of radiological and computed tomography results of elbow joint in dogs - Canan Kondak Yılmaz; Kurtuluş Parlak; Elgin Orçum Uzunlu; Mustafa Yalçın; Mustafa Arıcan (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to evaluate and compare clinical, radiological and computed tomography results in the early diagnosis of elbow dysplasia which might be a major pathological problem in elbow joint in dogs. Materials and Methods: A total of Twelve dogs prone to articulatio cubiti dysplasia were used as a materials. Dogs were subjected to routine systemic and clinical examinations. The stance analyzer was then used to measure unequal weight distribution in the extremities of the dogs. Radiological examinations of the cases were performed with and medio-lateral and cranio-caudal positions in the flexion and full extension of the elbow joints. The elbow joints of the cases were examined by computed tomography (CT). Results: Cranio-caudal radiological view of elbow joint revealed condylus laterale and mediale humerale, olecranon, fossa olecrani, medial and lateral coronoid process. Ununited anconeal process and separation from the subratrochlear foramen were anatomically observed with medio-lateral and medio-lateral flexion on radiological views. The ununited anconeal process can be definitively identified in the medio-lateral, medio-lateral flexion position. Fragmented or ununited medial coronoid process diagnosis is confirmed by computed tomography in order to obtain more precise information, as the radiological examination may be misleading due to the superposition of the anatomical elements. In particular, it was concluded that osteochondrosis cases could be diagnosed by both diagnostic tools. Conclusion: The ununited anconeal process is thought to be easily identifiable by radiological examination, and that CT does not need to be used for this purpose. However, the diagnosis of fragmented or ununited medial coronoid process revealed that CT is superior to radiological imaging.